Learning Management of Qur'anic Tahsin Instruction Using the Iqra Method for Junior High School Student - Muhammad Nazir; Jamal Fahri; Septuri (Dirasah: Jurnal Pendidikan Islam, 2026)
This study examines how learning management shapes the effectiveness of the Iqra method in Qur'anic Tahsin instruction for junior high school students, using a Systematic Literature Review (SLR) approach. The SLR design enabled the identification, critical appraisal, and synthesis of empirical and conceptual studies addressing the implementation of the Iqra method in Tahsin instruction at the lower-secondary level. Twenty relevant journal articles published between 2019 and 2024 were retrieved from Google Scholar and analyzed following a structured identification, screening, and eligibility procedure. The review sought to evaluate the effectiveness of the Iqra method in improving students' Qur'anic reading ability, with particular attention to tajwid (recitation rules) and makharij al-huruf (points of articulation), and to map the managerial factors that support or hinder its implementation. The synthesis shows that the Iqra method consistently improves students' Qur'anic reading fluency and accuracy, and that this effectiveness is strongly mediated by learning management practices—particularly instructional planning, time allocation, ability-based grouping, the integration of digital learning media, and a supportive school environment. Persistent challenges include heterogeneous student ability, limited instructional time within the curriculum, and insufficient teacher training in adaptive classroom management. The review concludes with recommendations for differentiated instruction, technology integration, and sustained teacher professional development to strengthen Tahsin learning outcomes at the junior high school level.